The Influence of Information Quality on Learning Satisfaction With The Use of Chatgpt as A Mediating Variable - Selina Elga Nurvina; Muhammad Fahmi Johan Syah (Dinasti Publisher, 2025)
Digital transformation in education has significantly changed how students access information and achieve learning satisfaction. One of the most impactful innovations is the use of artificial intelligence, particularly ChatGPT, to support the learning process. This study aims to examine the effect of information quality on learning satisfaction with the use of ChatGPT as a mediating variable. The research was conducted on undergraduate students of the Faculty of Teacher Training and Education at Universitas Muhammadiyah Surakarta in the 2024 academic year who had used ChatGPT in academic activities. A total of 100 respondents were selected using purposive sampling. The data analysis method employed was Partial Least Squares Structural Equation Modeling (PLS,SEM) using SmartPLS software. The results indicate that information quality significantly influences learning satisfaction, both directly and through the mediation of ChatGPT usage. Additionally, information quality has a strong and significant effect on the intensity of ChatGPT use, and ChatGPT usage itself contributes positively to students’ learning satisfaction. However, the evaluation of the measurement model reveals that discriminant validity and overall model fit have not been fully achieved, suggesting the need for model refinement in future research. This study contributes to understanding the integration of AI,based technologies in education and highlights the importance of enhancing information quality to foster a more adaptive and effective learning.